Effects of Maturity on Chemical Composition and Antioxidant Activity of Sacha Inchi (Plukenetia volubilis L.) Cultivated in NorthernThailand - SINGANUSONG, Riantong; JIAMYANGYUEN, Sudarat (Walailak Journal of Science and Technology (WJST), 2020)
Sacha inchi is cultivated commercially in Thailand for its edible kernels and oil. Highest quality sacha inchi is normally associated with highest oil content. Samples of 3 maturity stages: green, greenish brown, and brown and dry, were collected from 2 different harvests and comparisons were made based on composition and antioxidant analysis. In each harvest, all 3 stages were collected from the Phitsanulok and Chiang Rai provinces. There were 12 samples plus 2 controls. As maturity increased, moisture content of samples decreased, while oil content increased. Oil content ranged from 38.15 - 48.81 g/100 g. Protein content ranged from 16.23 - 18.98 g/100 g. Fibre content was 14.50 - 22.24 g/100 g, ash content was 2.70 - 3.06 g/100 g, and carbohydrate content was 7.70 - 19.47 g/100 g. The total phenolic content (TPC) was 103 - 385 mg/100 g, and antioxidant activity was 9.36 - 13.72 % for DPPH and 5,803.99 - 10,700 mg Trolox equivalent for FRAP. Average SFA, MUFA, and PUFA contents were 3.35, 4.63, and 30.91 g/100 g, respectively. Most common FA was omega-6 PUFA, followed by omega-3 and omega-9. Omega-6 to omega-3 ratio was 1.12 - 1.56. Samples with highest oil content were brown and dry samples harvested from Chiang Rai (47.26 g/100 g oil) and Phitsanulok (46.37 g/100 g oil), which were selected to test for amino acids and vitamin E. Nineteen amino acids were detected, with lysine, tyrosine, leucine, and glutamic acid predominant. Vitamin E content was 1.02 - 1.42 mg/100 g. For highest quality and greatest benefits to health, sacha inchi should be harvested when the shuck is brown and dry.